Centralized synthetic inertia control of inverter-based thermostatically controlled load clusters for grid frequency regulation - Te Zhou; Meng Zhou; Shuai Wang; Zhi Li; Yang Han; Tomislav Capuder; Ning Zhang (iEnergy)
As the development of new power systems progresses, the inherent inertia of power systems continues to diminish. Centralized frequency regulation, which relies on rapid communication and real-time control, can enable inverter-based thermostatically controlled load (ITCL) clusters to provide virtual inertia support to the power grid. However, ITCL clusters exhibit significant discrete response characteristics, which precludes the direct integration of load-side inertia support into the synchronous unit side. To address this issue, this paper elaborates on the existing technical framework and analyzes the underlying causes of the problem. It proposes a timestamp allocation mechanism for ITCL cluster control instructions, ensuring that many ITCL terminals can be triggered at staggered times, thereby allowing the load cluster power to adhere to the inertia analog control law at any moment. Building on this foundation, the paper further examines the impact of the inertia response delay of ITCL clusters, which is based on centralized frequency regulation, on the stability of the power system. A design scheme for inertia analog control parameters is proposed, taking into account dual constraints, frequency stability and load cluster regulation capacity. Finally, the feasibility and applicability of the proposed mechanism and parameter design scheme are investigated through simulations conducted via MATLAB/Simulink.